Od soczewki do siatkówki. Z dziejów badań nad poszukiwaniem elementu recepcyjnego oka - Grzybowski, Andrzej; Witczak, Włodzimierz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
In the historical context, theories of vision reflected gradual recognition of human anatomy, physiology and histology, including also the development of optics. Ancient Greeks and Romans believed that the lens is the part of the eye responsible for light reception. It was followed by misconception of the central localization of the lens within the eye. This approach outlasted until the 16th century. Then, due to such scholars as Leonardo da Vinci, Felix Platter, Hieronymus Fabricius d’Aquapendente, Johannes Kepler and Christopher Scheiner, the previous concepts concerning the role of the lens were gradually questioned, and finally its role was limited to light refraction and focusing the light beam to the bottom of the eye. In the 17th century appeared a controversy concerning the two membranes – retina and choroidea – and question which one of them is responsible for the reception of light. Finally, it was only at the onset of the 19th century when the true function of retina was confirmed.